PEMETAAN PERCERAIAN TENAGA KERJA INDONESIA (TKI) (STUDI KASUS DI KABUPATEN PONOROGO) - Nasution, Robby Darwis (Jurnal Penelitian Kesejahteraan Sosial, 2019)
Abstract Â Ponorogo is the largest contributor of migrant workers (TKI) in East Java in 2016. While in 2015, the number of job seekers registered was 6,704 people, consisting of men 2,355 people and women 4,349 people. The large number of TKIs originating from Ponorogo turned out to also leave many problems both related to the families left behind. Divorce cases in Ponorogo Regency as one of the districts with the largest contributor to Indonesian labor migrants in East Java are still considered high where based on data from the Ponorogo Religious Court, throughout 2008 there were 1,331 divorce cases handled and up to June 2009 the number of divorce cases reached 651 more. So from that it is very interesting to see more about the mapping of divorce from Indonesian Workers from Ponorogo Regency. In this study will use descriptive qualitative research methods with the determination of informants using snowball sampling. The results of this study are an increase in divorce of migrant workers from 2017 to 2018 by 200%, where the average migrant worker applying for divorce works in Hong Kong and Taiwan. The government has taken many anticipatory steps to tackle this divorce but it turns out that TKI divorces are indeed very complex because they are related to individual internal problems and are influenced by internal and external factors of TKI. Â Keywords: Divorce, Indonesian Workers (TKI), Ponorogo Regency Â Abstrak Â Ponorogo merupakan penyumbang buruh migran (TKI) terbesar di Jawa Timur pada tahun 2016. Sedangkan pada tahun 2015, jumlah pencari kerja yang terdaftar 6.704 orang, yang terdiri dari laki-laki 2.355 orang dan perempuan 4.349 orang. Besarnya jumlah TKI asal ponorogo ini ternyata juga menyisakan banyak permasalahan baik terkait dengan keluarga yang ditinggalkan. Kasus perceraian di Kabupaten Ponorogo sebagai salah satu Kabupaten dengan penyumbang TKI terbesar di Jawa Timur dinilai masih cukup tinggi dimana berdasarkan data dari Pengadilan Agama Ponorogo, sepanjang tahun 2008 terdapat 1.331 kasus perceraian yang ditangani dan hingga Juni 2009 jumlah kasus perceraian yang telah masuk mencapai 651 kasus lebih. Maka dari itu sangat menarik sekali jika melihat lebih jauh tentang pemetaan perceraian Tenaga Kerja Indonesia asal Kabupaten Ponorogo. Dalam penelitian ini akan menggunakan metode penelitian deskriptif kualitatif dengan penentuan informan menggunakan snowball sampling. Hasil dari penelitian ini adalah terjadi peningkatan perceraian TKI dari stahun 2017 sampai dengan tahun 2018 sebesar 200% dimana rata-rata TKI yang mengajukan perceraian bekerja di Hongkong dan Taiwan. Pemerintah sudah melakukan banyak langkah antisipatif untuk menanggulangi perceraian ini tetapi ternyata perceraian TKI memang sangat kompleks karena terkait dengan masalah internal individu dan dipengaruhi oleh faktor internal dan eksternal dari TKI. Â Kata Kunci : Perceraian, Tenaga Kerja Indonesia (TKI), Kabupaten Ponorogo